PENGENDALIAN KINERJA BIAYA DAN WAKTU PADA PROYEK HOTEL SEMINYAK - Made Parimana Yustiawan; Putu Gede Suranata; Ni Komang Armaeni (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
ABSTRACT During the construction period there is often an incompatibility schedule between the planning and implementation in the field. Therefore, the need of doing control performance in order for the project to run in accordance with the contract time. To find out the performance of the project, can be used earned value method. The data that are required to analyze the performance using earned value are BCWP, BCWS, and ACWP. The control of construction project could be done by acceleration. Time Cost Trade Off method is used to obtain the most efficient and effective results. The purpose on this study is to evaluate a project that is experiencing delays in achievements. Based on the contract, if the contractor unable to finish the project in accordance with time that is given in the contract, the contractor will be charged with penalty of 0.1% of the agreed price. After being evaluated at week of 13th using earned value, it turns out that the project is experiencing delays where the project should be completed within 300 days and it turns out 314 days with the cost required to complete the project is IDR.16,139,554,490.00. In order for the project to be completed in accordance with the contract time, the writer does the acceleration by doing additional work time for 3 hours. By using time cost trade off method, the writer could determine the work to be accelerated by selecting from the lowest slope value on the critical path so that it could obtain the most efficient cost to complete the project on time. From the analysis result using time cost trade off, it is found that the acceleration resulting in the minimum total cost to complete the project on time is IDR.16,157,311,547.00. By using the additional working hours, this project could be completed with the most optimal time of 259 days with the total cost required is IDR.16,329,053,679.00. Keywords: earned value, control, time cost trade off